The non-canonical inflammasome activators Caspase-4 and Caspase-5 are differentially regulated during immunosuppression-associated organ damage - Ghait, Mohamed; Duduskar, Shivalee N.; Rooney, Michael; Häfner, Norman; Reng, Laura; Göhrig, Bianca; Reuken, Philipp A.; Bloos, Frank; Bauer, Michael; Sponholz, Christoph; Bruns, Tony; Rubio, Ignacio (Frontiers in Immunology, 2023)
The non-canonical inflammasome, which includes caspase-11 in mice and caspase-4 and caspase-5 in humans, is upregulated during inflammatory processes and activated in response to bacterial infections to carry out pyroptosis. Inadequate activity of the inflammasome has been associated with states of immunosuppression and immunopathological organ damage. However, the regulation of the receptors caspase-4 and caspase-5 during severe states of immunosuppression is largely not understood. We report that CASP4 and CASP5 are differentially regulated during acute-on-chronic liver failure and sepsis-associated immunosuppression, suggesting non-redundant functions in the inflammasome response to infection. While CASP5 remained upregulated and cleaved p20-GSDMD could be detected in sera from critically ill patients, CASP4 was downregulated in critically ill patients who exhibited features of immunosuppression and organ failure. Mechanistically, downregulation of CASP4 correlated with decreased gasdermin D levels and impaired interferon signaling, as reflected by decreased activity of the CASP4 transcriptional activators IRF1 and IRF2. Caspase-4 gene and protein expression inversely correlated with markers of organ dysfunction, including MELD and SOFA scores, and with GSDMD activity, illustrating the association of CASP4 levels with disease severity. Our results document the selective downregulation of the non-canonical inflammasome activator caspase-4 in the context of sepsis-associated immunosuppression and organ damage and provide new insights for the development of biomarkers or novel immunomodulatory therapies for the treatment of severe infections.